EFFICACITE DES STRUCTURES DE COGESTION DES RESSOURCES NATURELLES DE LA FORET CLASSEE DES MONTS KOUFFE - GIBIGAYE ADAM, MOUSSA (My University, 2013)
The perennisation of the assets of the forest projects constitutes a problem. This study evaluates the effectiveness of the structures charged to manage the natural resources of the Monts Kouffé after project PAMF. These structures were subjected to an car-evaluation. The average score of realization of the activities varies from 0,02 to 3,35 and that of effectiveness of the structures of 0,72 to 2,71 points, values below mean. The structures are statistically homogeneous with the threshold of 5 %. None of them was not effective.
Keywords: Effectiveness; coadministration; classified forest; Benin